Interview with Mr. Shanker Prasad Koirala, Secretary, Ministry of Water Resources - Thanju, Jeewan Prasad (Hydro Nepal: Journal of Water, Energy and Environment, 2009)
Mr. Shanker Prasad Koirala granted an interview to Mr. Jeewan P. Thanju, Editor-in-Chief of HYDRO Nepal. He is determined for rapid development of hydro power sector in Nepal by mustering support from all quarters. Excerpts from an interview:- Hydro Nepal: Journal of Water, Energy and Environment Issue No. 3, January, 2008 Page 57-59